NovaGenesis: Aplica????o de uma arquitetura de internet do futuro para sistemas ciber-f??sicos na ind??stria 4.0 - Pivoto, Diego Gabriel Soares (2021)
The industrial scenario has been undergoing exponential changes due to the increasing production demand and the Industry 4.0 (I4.0) initiative, which proposes the factory digitization. Among the various emerging technologies, it can be can highlighted the Industrial Internet of Things (IIoT) and the Cyber-Physical System (CPS), making the use of Internet in industrial environments a mark of this new industrial era. In this context, researchers are developing IIoT systems and CPSs capable of virtualizing network assets and integrating them with other manufacturing sectors and industries, ensuring the interoperability among different architectures. Due to the current Internet limitations and need for advanced architectures for supporting emerging and legacy technologies, this work aims to use a Future Internet (FI) architecture called NovaGenesis (NG) for the development of a CPS in I4.0 based on the Reference Architecture Model Industry (RAMI) 4.0. The evaluation methodology used was based on the performance of laboratory experiments with equipment used in the field provided by Intituto Nacional de Telecomunica??c??oes (Inatel) and the development of tests related to digitization and data remote monitoring of industrial devices in real-time. The results of the tests show the potential feasibility by using the NovaGenesis architecture to develop an Industrial Cyber-Physical System (ICPS) meeting the needs of the RAMI 4.0 model, combining I4.0 and FI initiatives to develop an efficient means of digitizing devices in the industrial environment